La figura que trajo la ley 1437 de 2011, frente a la extensión de la jurisprudencia del Consejo de Estado (2016)
With this research we intend to show the legal concept implemented in the Code of Administrative Procedure and Administrative (Law 1437 of 2011), in accordance with Articles 10, 102, 269, 270, 271, which they are the basis of the investigation. The Legitimation and procedure to take part in a process are written to know when to go to the competent authority and assert their rights violated .The extensions of the jurisprudence of the State Council have mandatory application to administrative officials and judges-law the citizen meets the requirements of law, creating new formal source of law. The origin of this research arises from the entry into force of this CPACA Code or law 1437, 2011 / January 18, whether or not applicable by the administrative or judicial authority the extension compulsory Decisions by the Council referring to cases Repair direct Article 140 of this law. Articles (1, 4, 13, 29, 31.209, 230, 237) of Constitution as a criterion of equality law and jurisprudence chords to the subject, The greatest satisfaction of this work is to set a precedent about the legality of the article 230 justified by the judges rule of law as constitutional provision Colombia taking Social State of Rights